2006
DOI: 10.1637/7418-080705r.1
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus-Mediated Gene Expression in Chicken Primary Cells

Abstract: A recombinant baculovirus was constructed containing an expression cassette with a reporter gene, green fluorescent protein, directed by a constitutive mammalian promoter: a human cytomegalovirus immediate early promoter/enhancer (CMV-IE). High titer virus was prepared with ultracentrifugation. Efficient gene delivery and expression were observed in the virus-treated chicken primary culture, myoblast cells, and whole embryonic fibroblast cells. It was noticed that an addition of sodium butyrate (a selective hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…In general, improvements in transient gene expression are multiplex with the most prominent to be the transfection efficiency, the maximum cell density and the concentration of protein enhancers (Jardin et al 2008). Other enhancers are sodium butyrate (Leisy et al 2003;Mahonen et al 2007;Ping et al 2006) and trichostatin A (Spenger et al 2004). More recently proto-oncogenes, cell cycle control genes, growth factor genes and anti-apoptotic genes have been used to improve production hosts or transient expression (Wurm 2004;Backliwal et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In general, improvements in transient gene expression are multiplex with the most prominent to be the transfection efficiency, the maximum cell density and the concentration of protein enhancers (Jardin et al 2008). Other enhancers are sodium butyrate (Leisy et al 2003;Mahonen et al 2007;Ping et al 2006) and trichostatin A (Spenger et al 2004). More recently proto-oncogenes, cell cycle control genes, growth factor genes and anti-apoptotic genes have been used to improve production hosts or transient expression (Wurm 2004;Backliwal et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on published studies (Dorner et al 1989;Chen et al 2002;Li and Li 2006;Zhao et al 2006;Ping et al 2006;Song et al 2006), sodium butyrate (NaBu), is a histone deacetylase inhibitor, affecting the chromatin structure and leading to the destabilization of nucleosomal structure. As a consequence, the NaBU influence on chromatin exposure may facilitate binding of transcription factors to DNA resulting in an increased and deregulated cell protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the transfection procedure, aiming the introduction of foreign DNA into cells, is an important step. The calcium phosphate method has been recommended for gene transfection of S2 cells (Van der Straten et al 1989) but procedures based on liposome reagent have been reported to be more efficient (Han 1996;Park et al 1999;Shin and Cha 2002) Besides the metallothionein promoter induction by copper sulfate (CuSO 4 ) (Huang et al 2004) it has been studied the enhancement of gene expression by agents, such as the sodium butyrate (NaBu), a histone deacetylase inhibitor that lead to chromatin exposure and allow the transcriptional factors binding and increased gene expression (Dorner et al 1989;Li and Li 2006;Zhao et al 2006;Ping et al 2006;Song et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After a long history, in 1985, first successful in vitro gene transfer by a recombinant baculovirus was accomplished by Carbonell et al (1985) that made baculovirus a tool in gene transfer technology, especially in the over expression of cloned genes (O'Reilly et al 1992). Since then, the recombinant baculoviruses have been successfully used for gene transfer in various eukaryotic cells including those of fishes (Smith and Summers 1989;Leisy et al 2003;Wagle and Jesuthasan 2003;Wagle et al 2004), chicken and duck (Ping et al 2006;Song et al 2006), fruit fly (Oppenheimer et al 1999; Lee et al 2000), honey bees (Ando et al 2007), shrimp (Lu et al 2005;Syed Musthaq et al 2009; Syed Musthaq and Kwang 2011) rabbit (Airenne et al 2000), monkey (Tani et al 2001) and human (Hofmann et al 1995;Kost and Condreay 2002). Besides, recombinant baculovirus has been used for gene therapy (Luo et al 2011;Zhao et al 2012), and vaccine production (van Oers 2006;Treanor et al 2007;Hu et al 2008;Cox 2012).…”
Section: Introductionmentioning
confidence: 99%